THE STUDENTS’ ENGLISH PRAGMATIC COMPETENCE IN UNDERSTANDING CROSSCULTURAL COMMUNICATION: A STUDY AT XI GRADE STUDENT OF SMK NEGERI 1 BATULAYAR - Mayanto, Derah (Lingual Journal of Language and Culture, 2016)
This paper investigates the students’ English pragmatic competence in understanding crosscultural communication. There were eighteen communicative situations designed in three different speech acts namely; handling complaint, request and refusal. The situations presented were very similar to the authentic situation that students found during the job orientation for six months in tourism industry. Three instruments were used in collecting the data; questionnaires, discourse completion tests (DCTs) and interview. The multiple choice questionnaire was used to investigate the students’ pragmatic understanding in three deferent speech acts. Meanwhile DCTs was used to investigate the students’ pragmatic knowledge in giving response to the given situations related to three different speech acts. Interview question was used to clarify the missing information and to strengthen the reason why such responses were given in questionnaire and in DCTs. The sample of this study was 92 XI Grade students from Hotel Accommodation Program (AP) at SMK Negeri 1 Batulayar. The result show that the students ability in understanding pragmatic is considered very low, they only can understand the utterance from the literal meaning of words and phrases, but the implied meaning of some particular utterances were uneasy to deal with. It is seen from the reported data that the average of the students’ responses in understanding pragmatics of the three different speech acts is only 12.7%. The second three different speech acts in discourse completion test (DCTs) was also about giving response to the complaint, request and refusal. DCTs were used to investigate the students’ ability in using their pragmatic knowledge to response the nine situational communicative designed. The finding show that the students’ ability in giving the written response were vary and less impressive. The written responses in three different speech acts prompt were potentially led to a pragmatic inability in maintaining the smooth conversation in various situations.
Keywords: pragmatic competence, communicative situational designed, lexical items, basic formulaic sequence, discourse completion test